Collapsing Focal Segmental Glomerulosclerosis and Acute Oxalate Nephropathy in a Patient With COVID-19: A Double Whammy. (October 2020) - Malhotra, Varun; Magoon, Sandeep; Troyer, Dean A.; McCune, Thomas R.
As COVID-19 (coronavirus disease 2019) spreads across the world multiple therapeutic interventions have been tried to reduce morbidity and mortality. We describe a case of collapsing focal sclerosing glomerulosclerosis (FSGS) and acute oxalate nephropathy in a patient treated with high-dose intravenous vitamin C for severe COVID-19 infection. Collapsing FSGS has been described in patients with COVID-19 infection associated with APOL-1; however, this case had collapsing FSGS developing in low-risk heterozygous APOL-1 variant, and we postulate that the intensity of the COVID-19 cytokine storm overwhelmed the protective state of APOL-1 heterozygosity. This case illustrates the importance of assessing the risk and benefit of planned therapeutic interventions on a case-by-case basis especially when there are still so many unknowns in the management of COVID-19 infection. Strong consideration should be given for performing a renal biopsy in patients who develop multifactorial acute kidney injury.